How do Socioeconomic Factors Shape Health Inequalities? A Multilevel Analysis of Access to Healthcare in Middle-income Cities in China - Liu, Lu (International Journal of Social Sciences and Public Administration, 2025)
BACKGROUND: Globally, more than half of the population still lacks access to basic health care, and economic status is one of the key factors influencing this. Morbidity and mortality rates of non-communicable diseases (NCDs) and the low survival and high disability rates of out-of-hospital cardiac arrest (OHCA) are closely related to inequitable allocation of healthcare resources. OBJECTIVE: To analyse the broad impact of socio-economic factors on the health of the population, especially the health disparities caused by regional inequalities in the allocation of healthcare resources in Shaoxing, and to explore the challenges to health equity in China. METHODS: Based on China's 2020 census data, Zhejiang Province statistical data, Shaoxing City Statistical Yearbook, Shaoxing City prehospital emergency care quality control indicators, and public information of the Health and Wellness Committee. RESULTS: Yuecheng District is economically more developed, with 9 general hospitals, 12,723 health technicians, 4,844 medical practitioners, 87.95 beds/per 10,000 people, 61.58 doctors/per 10,000 people, and a pre-hospital emergency response time of 7´30´´ to 7´58´´ in the urban area. Xinchang County has a low economic income and a large gap between urban and rural per capita income, with 4,337 health technicians, 1,492 practicing physicians, and a prehospital emergency response time of 12´43´´ to 22´9´´. CONCLUSIONS and RECOMMENDATIONS: Economic factors are the core drivers of inequality in regional medical resource allocation, with higher-income regions having more concentrated and better-configured medical resources. Economic levers are used to regulate regional healthcare resource allocation, reduce health disparities, and promote equitable and sustainable health development.